Assessment of the microbiological quality of bottled water and protected spring water in Bushenyi district, Uganda - Nkatha Micheni, Lisa; Nsiko, Peter; Eilu, Emmanuel; Echoru, Isaac; Maniga Nyabayo, Josephat (Scholars Academic Journal of Biosciences, 2015)
Whereas microbiological quality of bottled drinking water is routinely monitored for reasons of legal compliance, microbial numbers in spring water are grossly understudied. Safety of water is a major public concern. However, the portability status of each type of water is a major concern to the public health. This study was carried out to assess of the microbiological quality of bottled and protected spring water in Ishaka-Bushenyi District. A total of 33 samples of bottled water and 8 samples of protected spring water were analysed using the Membrane Filtration Method. This method involved filtering the samples through a membrane filter (size 25um), culturing on lactose (TTC) with sodium heptadecylsulfate media and performing biochemical tests (oxidase and Indole) for confirmation of coli forms and E. coli respectively. Four (50%) of the protected springs showed growth of typical yellow colonies on lactose agar media. The presence of E. coli signified that protected springs were being contaminated with fresh faecal matter. However, no bottled water showed any signs of contamination (0%) with total coli forms or E. coli. There was a strong association (P= 0.01) between water source and water quality. Bottled water sold in Ishaka, Bushenyi District of Uganda showed high quality standards while protected spring water showed significant level of contamination with E. coli which could potentially cause disease to the consumers. Therefore all stakeholders in public health should come together to look into the matter of increasing access cheap and safe water other than the unsafe water from the so called ―protected springs‖.
Keywords: Bottled water Uganda; Water testing Uganda; Microbiological water assessment Uganda